ChemInform Abstract: Synthesis and Antibacterial/Antitubercular Activity Evaluation of Symmetrical trans‐Cyclohexane‐1, 4‐diamine Derivatives. Issue 12 (25th March 2014) - Kumar, Nitin; Kapoor, Ekta; Singh, Ramandeep; Kidwai, Saqib; Kumbukgolla, Widurana; Bhagat, Sunita; Rawat, Diwan S.
Abstract A library of symmetrical trans‐cyclohexanediamine derivatives (IV) (27 examples) are synthesized and evaluated for their antibacterial activities.